2015
DOI: 10.1016/j.amjmed.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Patient Self-administered Substance Use Screening Tool for Primary Care: Two-site Validation Study of the Substance Use Brief Screen (SUBS)

Abstract: Background Substance use screening is widely encouraged in healthcare settings, but the lack of a screening approach that fits easily into clinical workflows has restricted its broad implementation. The Substance Use Brief Screen (SUBS) was developed as a brief, self-administered instrument to identify unhealthy use of tobacco, alcohol, illicit drugs, and prescription drugs. We evaluated the validity and test-retest reliability of the SUBS in adult primary care patients. Methods Adults age 18-65 were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 64 publications
1
67
0
Order By: Relevance
“…Two scoring cutoffs were used in our analysis of the SUBS. First we applied the standard SUBS cutoff of “never” as a negative screen and any other response as a positive screen (McNeely et al, 2015). Second, we examined the results designating a higher SUBS cutoff of “three or more days” as a positive screen, and other responses as a negative screen.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two scoring cutoffs were used in our analysis of the SUBS. First we applied the standard SUBS cutoff of “never” as a negative screen and any other response as a positive screen (McNeely et al, 2015). Second, we examined the results designating a higher SUBS cutoff of “three or more days” as a positive screen, and other responses as a negative screen.…”
Section: Resultsmentioning
confidence: 99%
“…The SUBS (McNeely et al, 2015) (Fig. 1) was developed as a brief, self-administered instrument to identify unhealthy use of tobacco, alcohol, illicit drugs, and non-medical use of prescription drugs (4 total questions), and has been validated in the primary care setting (McNeely et al, 2015; National Institute on Drug Abuse, NIDA, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other studies over the past decade have shown a wide range (3-26 %) of reported drug use in primary care. 8,9 The prevalence and severity of chronic pain and painrelated dysfunction in patients who screen positive for the full spectrum (at-risk use to substance use disorders) of drug use (Illicit, prescription misuse) in primary care is unknown. Because alcohol, 10 many illicit drugs (e.g., heroin, marijuana) and prescription opioids have analgesic properties, it is possible that patients are using these drugs to self-medicate pain.…”
Section: Introductionmentioning
confidence: 99%